The effect of mining foreign direct investment inflow on the economic growth of Zimbabwe - Plaxedes Gochero; Seetanah Boopen (Journal of Economic Structures, 2020)
The study employs the autoregressive distributed lag (ARDL) approach to examine the relationship between foreign direct investment (FDI) in the mining sector on the Zimbabwe economy, while controlling for both non-mining FDI and domestic investment. Using data over the period 1988-2018, this research results show that foreign direct investment in the mining sector has a significant positive relationship with the country's GDP in the long run. Mining FDI is revealed to have relatively higher effects as compared to FDI in non-mining sector and domestic investment. The short-run analysis observed that mining FDI as well as non-mining and domestic investment still has positive and significant impacts on growth but at a relatively lower extent. This implies that it takes some time for such investments to have their full effect on the economy.
Keywords: 330; Foreign direct investment inflow; The Zimbabwean mining sector